One year follow-up outcomes of endovascular treatment for aortic dissection with a partial micropore stent graft in which fixation of the stent is done in zone 0: A pivotal trial first in human. Issue 161 (April 2023) - Teng, Biyun; Chen, Zhen; Ao, Yuxiang; Zhao, Yu; Li, Fenghe; Fu, Qining; Zhang, Wei; Wang, Zhe
Abstract: Objective: This study aimed to verify the efficacy and safety of the treatment for patients diagnosed with DeBakey type I and type III thoracic aortic dissections using a partial micropore stent graft. Methods: We conducted a retrospective analysis of 32 patients who suffered from thoracic aortic dissection and underwent endovascular repair using a partial micropore stent graft at our center between December 2018 and January 2020. Results: The technical success rate for 32 patients was 100 %, while no 30-day mortality was observed. In the 30 patients finished follow-ups, 30 (mean: 1 per patient) micropore stents were implanted, while the openings of 90 (mean: 3 per patient) aortic arch branches were covered by the stents. After more than 12 months follow-up, 26 (86.7 %) of the 30 patients presented with a complete thrombosis in the false lumen, and 4 (13.3 %) patients presented with a partial thrombosis in the false lumen. All 90 aortic arch branches were patent. No aortic arch branch artery stenosis or occlusion was observed. Conclusions: The outcomes obtained during 12 months of follow-up suggested that performing endovascular repair for thoracic aortic dissection patients with a partial micropore stent graft is safe and effective, maintaining the patency of aortic arch branch vessels.